Only strict quarantine measures can curb the coronavirus disease (COVID-19) outbreak in Italy, 2020 - Sjödin, Henrik; Wilder-Smith, Annelies; Osman, Sarah; Farooq, Zia; Rocklöv, Joacim (Eurosurveillance, 2020)
Several Italian towns are under lockdown to contain the COVID-19 outbreak. The level of transmission reduction required for physical distancing interventions to mitigate the epidemic is a crucial question. We show that very high adherence to community quarantine (total stay-home policy) and a small household size is necessary for curbing the outbreak in a locked-down town. The larger the household size and amount of time in the public, the longer the lockdown period needed.